Daya Saing dan Pertumbuhan Ekonomi Negara Berkembang ASEAN - Fadeli Yusuf Afif; Ukhti Ciptawaty (Jurnal Ekonomi Pembangunan, 2020)
The purpose of this study is to look at the condition of the country's competitiveness and its influence on ASEAN economic growth. The data used consists of panel data consisting of time series data for 2009 - 2019 and a cross section of five ASEAN countries with the highest level of competitiveness. The variables used are economic growth, competitiveness, labor participation, and foreign direct investment. The analysis tool used is panel data regression, the Fixed Effect Model (FEM). The results show that competitiveness, labor participation, and foreign direct investment have a positive and significant effect on economic growth in the five developing ASEAN countries. Keywords: ASEAN, Competitiveness, Economic Growth, and Fixed Effect Model (FEM).